Optimizing surgical management of uterine cervix disorders - I.Yu. Ilina; Yu.E. Dobrokhotova (LCC «Medicine-Inform», 2022)
I.Yu. Il'ina, Yu.E. Dobrokhotova Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to improve outcomes of the surgical management of cervix disorders by using a hemostatic agent with antimicrobial activity. Patients and Methods: the study included 47 women, 25-45 years of age, with CIN II/III to whom cervical radiofrequency ablation was performed. The main group comprised 26 (55.3%) patients. During the ablation procedure, a 1% aqueous solution of incomplete polyacrylic acid silver salt with integrated nanoparticles was used as an additional treatment for this group of patients. The control group consisted of 21 (44.7%) patients for whom the standard ablation technique was used. The assessed criteria included the clinical course and laboratory test results before and three months after the surgical treatment, as well as the bleeding rates. Results: in the main group of patients, the mean leucocyte number in the smear after the treatment was 9.2±1.2 per field of vision, in the control group - 18.5±2.9; pH of the vaginal discharge - 4.2±0.2 (from 3.8 to 4.5) and 4.7±0.2 (from 4.2 to 5.8), respectively. Intraoperative bleeding from the surgical wound which required additional manipulations was reported in 2 (7.7%) patients of the main group and 2 (9.5%) patients of the control group. Ten days after the surgery, one patient (3.8%) from the main group had complaints on heavy bloody vaginal discharge. Three (14,3%) patients from the control group had the same complaint 11-13 days after the surgery (3.7 relative risk, 95% confidence interval (CI) 1,0-18,2) which required the use of tranexamic acid as tablets for oral administration. Three months after the surgery the clue cells were found in one (3.8%) patient of the main group and in 7 (33.3%) patients of the control group (8.7 relative risk, 95% CI 1.2-16.5), and the fungal mycelia - only in 8 (38.1%) patients of the control group. Conclusion: the use of a 1% aqueous solution of incomplete polyacrylic acid silver salt with integrated nanoparticles during the cervical ablation resulted in a statistically significant reduction of the bleeding risk and improved the vaginal microflora profile in postoperative period. Keywords: cervical dysplasia, cervical excision, cervical conization, bacterial vaginosis, hemostatic agent, bleeding. For citation: Il'ina I.Yu., Dobrokhotova Yu.E. Optimizing surgical management of uterine cervix disorders. Russian Journal of Woman and Child Health. 2022;5(3):188-193 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-188-193.